Elderly with Autism: Executive Functions and Memory - Geurts, Hilde M. (Springer US, 2011)
Cognitive autism research is mainly focusing on children and young adults even though we know that autism is a life-long disorder and that healthy aging already has a strong impact on cognitive functioning. We compared the neuropsychological profile of 23 individuals with autism and 23 healthy controls (age range 51–83 years). Deficits were observed in attention, working memory, and fluency. Aging had a smaller impact on fluency in the high functioning autism (HFA) group than in the control group, while aging had a more profound effect on visual memory performance in the HFA group. Hence, we provide novel evidence that elderly with HFA have subtle neuropsychological deficits and that the developmental trajectories differ between elderly with and without HFA in particular cognitive domains.